Deeper H.E.S.S. observations of Vela Junior (RX J0852.0−4622): morphology studies and resolved spectroscopy - Abdalla, Hassan; Jankowsky, Felix; Mohamed, Mahmoud; Quirrenbach, Andreas; Rieger, Frank M.; Schwemmer, Stephanie; Wagner, Stefan; Cologna, Gabriele (Astronomy and astrophysics, 2018)
Aims. We study γ-ray emission from the shell-type supernova remnant (SNR) RX J0852.0−4622 to better characterize its spectral properties and its distribution over the SNR.Methods. The analysis of an extended High Energy Spectroscopic System (H.E.S.S.) data set at very high energies (E > 100 GeV) permits detailed studies, as well as spatially resolved spectroscopy, of the morphology and spectrum of the whole RX J0852.0−4622 region. The H.E.S.S. data are combined with archival data from other wavebands and interpreted in the framework of leptonic and hadronic models. The joint Fermi-LAT-H.E.S.S. spectrum allows the direct determination of the spectral characteristics of the parent particle population in leptonic and hadronic scenarios using only GeV-TeV data.Results. An updated analysis of the H.E.S.S. data shows that the spectrum of the entire SNR connects smoothly to the high-energy spectrum measured by Fermi-LAT. The increased data set makes it possible to demonstrate that the H.E.S.S. spectrum deviates significantly from a power law and is well described by both a curved power law and a power law with an exponential cutoff at an energy of Ecut = (6.7 ± 1.2stat ± 1.2syst) TeV. The joint Fermi-LAT-H.E.S.S. spectrum allows the unambiguous identification of the spectral shape as a power law with an exponential cutoff. No significant evidence is found for a variation of the spectral parameters across the SNR, suggesting similar conditions of particle acceleration across the remnant. A simple modeling using one particle population to model the SNR emission demonstrates that both leptonic and hadronic emission scenarios remain plausible. It is also shown that at least a part of the shell emission is likely due to the presence of a pulsar wind nebula around PSR J0855−4644.
Gesehen am 14.06.2019